2021
DOI: 10.3389/fphys.2021.614619
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Long-Term Head-Down Bed Rest in Understanding Inter-Individual Variation in Response to the Spaceflight Environment: A Perspective Review

Abstract: Exposure to the spaceflight environment results in profound multi-system physiological adaptations in which there appears to be substantial inter-individual variability (IV) between crewmembers. However, performance of countermeasure exercise renders it impossible to separate the effects of the spaceflight environment alone from those associated with exercise, whilst differences in exercise programs, spaceflight operations constraints, and environmental factors further complicate the interpretation of IV. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…To prevent these detrimental effects, the crewmembers of the International Space Station (ISS) perform daily exercise countermeasures, including treadmill running, cycling, and resistance training 3 . Due to the implementation of new exercise hardware and improvements of the in-flight exercise hardware and exercise prescriptions, μg-induced physiological deconditioning has been reduced, although variable inter-individual physiological responses to the exercise induced stimuli persist 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…To prevent these detrimental effects, the crewmembers of the International Space Station (ISS) perform daily exercise countermeasures, including treadmill running, cycling, and resistance training 3 . Due to the implementation of new exercise hardware and improvements of the in-flight exercise hardware and exercise prescriptions, μg-induced physiological deconditioning has been reduced, although variable inter-individual physiological responses to the exercise induced stimuli persist 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Anecdotal evidence has suggested that there is substantial individual variability in physiological variables following bed rest, including losses in muscle mass and function (Akima et al, 1997;Downs et al, 2016;Scott et al, 2021). However, the limited number of participants included in previous studies and the lack of an ambulatory control group prevented any firm conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Only large national or international space agencies can afford to run long-duration bed rest campaigns, which include a rather limited number of subjects per intervention group. The small sample size is indeed a significant constraint when exploring individual variability in bed rest studies (Scott et al, 2021). Furthermore, the lack of a genuine control group in bed rest studies, i.e., an ambulatory group, has limited the validity of any past attempt to detect individual responses to bed rest interventions (Atkinson and Batterham, 2015;Scott et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, studying humans in space can be viewed as an “experiment” to both identify in more detail how humans are regulated, and to identify and find solutions to enhance the health and safety of astronauts. Thus, from this “experiment,” it appears that human's exhibit heterogeneity in response to space conditions (reviewed in Scott et al, 2021 ), and that some of the same physiological systems affected by age/aging in many humans on Earth are also affected by space conditions (Ray, 1991 ; Vernikos and Schneider, 2010 ). As such, space flight may be viewed as “accelerated aging” (Ray, 1991 ; Vernikos and Schneider, 2010 ), or for the context of this discussion, acute (short term) and chronic (longer term) “deconditioning” based on removal from the boundary conditions of Earth and the mechanical activity required to maintain system integrity.…”
Section: The ‘Experiment” Of Space Flight As a Model Of Human “Deconditioning”mentioning
confidence: 97%